ChemInform Abstract: Copper‐Catalyzed Synthesis of Quinoline Derivatives via Tandem Knoevenagel Condensation, Amination and Cyclization. Issue 29 (June 2016) - Dhiman, Shiv; Saini, Hitesh Kumar; Nandwana, Nitesh Kumar; Kumar, Dalip; Kumar, Anil
Abstract: Knoevenagel condensation of 2‐bromobenzaldehydes with active methylene nitriles followed by copper‐catalyzed reductive amination and intramolecular cyclization affords 2‐aminoquinolines and 2‐arylquinoline‐3‐carbonitriles regioselectively.